Controlling the Wettability between Freestanding Electrode and Electrolyte for High Energy Density Lithium-Sulfur Batteries. Issue 1 (1st January 2018) - Hwang, Jang-Yeon; Kim, Hee Min; Sun, Yang-Kook
Abstract : The present study demonstrates how to improve the electrochemical performance and energy density of lithium-sulfur batteries based on controlling the wettability between the freestanding electrode and the electrolyte. First, to improve the volumetric energy density, we reduced the thickness of freestanding electrode by the applying pressure. Second, in order to improve electrolyte conductivity and wettability for pressed freestanding electrode, we reduced the viscosity of electrolyte solution by reducing the LiTFSI salt concentration. Through these controls, the Li-S cell is constructed from a pressed freestanding carbon nanotube-sulfur cathode, 0.5 M LiTFSI in DME/DOL with 0.4 M LiNO3 as a low-viscosity electrolyte (0.72 cP), and Li-metal foil as an anode. As a result, we can obtain a high discharge capacity of 1, 400 mAh g −1  at 0.1 C and excellent cycle retention of 95% after 80 cycles at 0.5 C in coin-type cell. In addition, scale-up (3 by 5 cm) pouch-type Li-S cell delivers a high discharge capacity of 500 mAh at 0.1 C with high gravimetric (954.4 Wh kg −1 cathode and >170 Wh kg −1 cell ) and volumetric (1, 150 Wh L −1 cathode and 515 Wh L −1 cell ) energy densities.